Individualization of training process as a leading construction of skiers` training component in preparation for higher achievements - Vorfolomeeva, L. A. (Physical Education of Students, 2013)
The aim was to improve the process of preparation of skiers in preparation for higher achievements. It is spotted urgency of introduction of individualization in the training process, the principles and directions of realization. It is offered individualized relationship seen as consistent instructional techniques and forms of management training athletes. It is proved that increasing individualization rationality of functional reserves of athletes and prevent early retirement. Argues that the correction of the training process is the need for the development of genetic expression in the function of an athlete and popular sports specialization. It is noted that during the preparation of the highest achievements of a fundamentally important point is to ensure that the conditions under which the period of maximum susceptibility athlete to achieve the best results with the same period of the most intense and complex in the coordination for training loads.